Grading system for SMK Dato Dol Said - Siti Hawa , Abd Mutalif (UTeM, 2010)
This project is about developing one computer system for a school which is SMK DATO DOL SAID. The development of this system is purposely to ease school management process and overcome problems faced by school organization during managing their student record. This system can handle database problem occurred such as loss of data, data cannot be analyzed and also large amount of data cannot be managed in one time. This system also is focusing in teacher key in student mark. This system is also developed with several modules provided purposely to overcome the problems faced. This system is developed by using Macromedia Dreamweaver 8 with PHP language and using MySQL as a database platform. The methodology that is used to develop this project is DBLC (database lifecycle Model). The study has been made during developing the system and among of the study are by searching on the internet about existing system that is similar with the system that want to be developed. The output from this project is one computer system that can help the school to manage their information process.